Identification and Resistance Testing of Bacteria Causing Nosocomial Infections in Surgery Inpatient Rooms - Grandiano Escool Tarigan; Nawan Nawan; Agnes Immanuela Toemon (Disease Prevention and Public Health Journal, 2023)
Background: Nosocomial infections are the most common infections that occur when patients are under medical care in hospitals. The most common pathogenic bacteria that cause nosocomial infections are Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, Enterobacter spp, and Klebsiella pneumonia. One of the factors causing a nosocomial infection is the environment. The spread of nosocomial infections in dr. Doris Sylvanus can occur in the surgical ward environment. Therefore, it is necessary to study and know the identification of bacteria and knowing the pattern of antibiotic resistance of bacteria that cause nosocomial infections in the surgical inpatient ward of dr. Doris Sylvanus Hospital. Methods: This type of research used an observational method with a descriptive approach. The research at dr Doris Sylvanus Hospital. The population is dahlia room which consisted of floors, sheets, patient beds, tables, and door handles. Results: Bacterial identification was Staphylococcus aureus at 13.4% and Staphylococcus non-coagulase at 10%, also found Gram-negative bacteria suspected Salmonella sp. 3.3% and other bacteria at 73.3% The results of the Trimethoprim-sulfamethoxazole antibiotic resistance test on S. aureus bacteria had a sensitivity of 50% and Oxacillin had a sensitivity of 75%, while the Trimethoprim-sulfamethoxazole resistance test results on S. non-coagulase bacteria had a sensitivity of 66.7% and Oxacillin had a sensitivity of 100%. Conclusion: The Trimethoprim-sulfamethoxazole antibiotic resistance test on S. aureus bacteria has moderate sensitivity and the Oxacillin antibiotic has a fairly high sensitivity while on S. non-coagulase bacteria have a fairly high sensitivity and oxacillin antibiotics have high sensitivity.